Automated Class Scheduling System - Gamale, Jeralyn M.; Anuta, Edward C.; Sayson, Zina D. (JPAIR Multidisciplinary Research, 2012)
The study tested the functionality of Automated Class Scheduling System in terms of speed, data handling, accuracy, security, stability and adaptability in making class schedules. This study was conducted in Bohol Island State University Main Campus, Tagbilaran City during the second semester of school year 2010-2011. The respondents of this study were the 6 expert instructors in the field of computer programming. They tested and evaluated the functionality of the program in terms of its design, accuracy, data handling, security, stability and adaptability. Another 8 instructors who are in charge of making class schedules determined the functionality of the system in terms of speed, accuracy, data handling, stability and adaptability of the software. Separate set of questionnaires were given to two groups of respondents. The study concluded that the manual and the automated class scheduling systems are both functional. However, the automated system is more functional because of its extra features which solve the primary problems in creating class schedules.